Catalytic hydrogenation of benzanthrone and its derivatives - Rintoul, Walter (The University of Edinburgh, 1937)
In recent years the study of benzanthrone and its derivatives has offered the organic chemist a subject for numerous investigations. During the course of a research into the Skraup reactions as applied to anthraquinone, Bally (Ber., 1905, 38, 194) originally prepared benzanthrone by heating anthraquinone with glycerol and sulphuric acid in the presence of a reducing agent. Although two interpretations of this reaction have been put forward, neither is in complete agreement with experimental evidence. The two inter- pretations, however, agree on one point, namely, that the reaction depends upon the condensation of anthrone (I) and acrolein (formed from the glycerol and acid), followed by elimination of water and hydrogen, to yield benzanthrone II.
The catalytic hydrogenation of benzanthrone and its derivatives